Casarett and Doull's toxicology the basic science of poisons - Klaassen, Curtis D., editor (McGraw-Hill Education, 2019)
"The gold-standard text on the science of poisons updated to capture the latest breakthroughs and developments Casarett & Doull's Toxicology: The Basic Sciences of Poisons is the most trusted all-in-one overview of the biomedical and environmental aspects of toxicology. Presented in full color, it delivers a skill-building review of the basic components of toxicology, including general principles, modes of action, and chemical-specific toxicity. Spanning the entire field, Casarett & Doull's is considered to be the ultimate authority in toxicology. The Ninth Edition has been extensively updated by each chapter author and is enhanced by the addition of all-new chapters on timely topics such as computational toxicology and auditory toxicology. The extensive use of tables, illustrations, and other visuals make the information easy to understand and remember"--Provided by publisher.